Telaah Kajian Urf terhadap Kebiasaan Wanita Berhias Saat Menghadiri Pesta Pernikahan Di Kecamatan Kotapadang - Perawati, Perawati; Yusefri, Yusefri; Nasution, Aida Rahmi (Berasan: Journal of Islamic Civil Law, 2024)
The purpose of this study is to answer the question of how to study urf on the habits of decorated women when attending weddings in Kotapadang District. Research methods used in empirical juridical research. Based on urf's review of the motivations of women's habits in decoration, it is seen from good motivation, one of which is to increase self-confidence, maintain the dignity of the husband, and appreciate the invitee, and see that the wedding party is a very special moment where many people gather, so in urf's view it is permissible because it provides good benefits and there is no prohibition to decorate as long as the decoration is in accordance with ekika the decoration of Islamic Shari'a. by not opening the aurat nor exaggerating and not showing the jewelry he wears other than what can be seen. The custom of decorated women while attending weddings is included in the Al-'urf al-'amali/fi'li.